Effects of litter and additional enrichment elements on the occurrence of feather pecking in pullets and laying hens – A focused review - Schreiter, Ruben (Vet Med Sci, 2019)
Severe feather pecking (SFP) is a serious problem in the egg production industry with regard to animal welfare and performance. The multifactorial causes of SFP are discussed in the areas of genetics, feeding, husbandry, stable climate and management. Several studies on the influence of manipulable material on the incidence of SFP in different environments and housing systems have been performed. This review presents current knowledge on the effects of litter and additional enrichment elements on the occurrence of SFP in pullets and laying hens. Because SFP is associated with foraging and feed intake behaviour, the provision of manipulable material in the husbandry environment is an approach that is intended to reduce the occurrence of SFP by adequate exercise of these behaviours. As shown in the literature, the positive effect of enrichment and litter substrate on SFP in a low‐complexity cage environment is evident. On the other hand, consistent results have not been reported on the influence of additional enrichment material in housing systems with litter substrate, which represent the most common type of husbandry in Northwestern Europe. Thus, further research is recommended.